EFFECTIVENESS OF THE IMPLEMENTATION OF PRODUCTIVE ECONOMIC BUSINESS PROGRAMS (UEP) BY THE SOCIAL SERVICE IN AN EFFORT TO PROSPER THE POOR IN THE VILLAGE OF MERAUKE REGENCY - Syahruddin Syahruddin; Wifin Pramudya (SOCIETAS, 2018)
The purpose of this study is to determine the effectiveness of the implementation of productive economic business programs (UEP) by the social service in an effort to prosper the poor in the village of Merauke regency. Data analysis uses qualitative methods and data analysis using three stages, namely data reduction, data presentation and conclusions. From the results of this study, researchers found that the economic business program by the social service in an effort to prosper the poor in the Merauke regency campungsota has not been effective because the trainings related to the program were not provided comprehensively to people who received productive economic business programs. As for other factors so that the program does not become effective because of the wrong lifestyle of people in the village of Sota, such as waking up on the side of the day and lazy lives. These constraints are due to the lack of awareness of the community in carrying out a program of peroductive economic business. Keywords: Effectiveness, Prosperity, Poo